Analisis Tren Kasus Kecelakaan Lalu Lintas Berbasis Dashboard Ambulance Hebat di Kota Semarang Tahun 2023-2025 - Sabrina Malika; Harsono Harsono; Ahmad Zaini; Wisnu Wardhana (Jurnal Ners, 2026)
Road traffic accidents remain a major public health concern in Semarang City, driven by high urban mobility and the dominant use of motorcycles. This study aims to describe the patterns, trends, and spatial distribution of traffic accidents based on data from the Ambulance Hebat Dashboard for the period 2023–2025 and to evaluate the role of the dashboard in supporting emergency response. A descriptive quantitative approach was employed using secondary dashboard data complemented by an interview with the Field Coordinator. The findings indicate a fluctuating trend, with 1,553 cases recorded in 2023, decreasing to 1,257 in 2024, and increasing again to 1,303 cases in 2025, with motorcycles being the most frequently involved vehicle type. Spatial analysis identified high-risk clusters in Semarang Tengah, Banyumanik, Candisari, and Pedurungan. The dashboard effectively facilitates real-time monitoring and response, although minor technical limitations in data synchronization persist. These results highlight the need for optimizing digital infrastructure, integrating interagency data, and prioritizing interventions in high-risk areas to strengthen urban road safety and emergency care performance.